Two new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from China - Rui-Jun Liu; Zhi-Shan Cao; Wei-Hai Li (European Journal of Taxonomy)
Two new species of the stonefly genus Sinacroneuria, S. aequalis sp. nov. and S. transversa sp. nov., are described and illustrated from the Fujian and Zhejiang provinces of China. These new taxa are compared with related congeners. A distribution map of the genus is also presented.